Thermodynamic properties of mixed-layer illite-smectite by calorimetric methods: Acquisition of the enthalpies of mixing of illite and smectite layers. (November 2019) - Gailhanou, H.; Blanc, P.; Rogez, J.; Mikaelian, G.; Kawaji, H.; Olives, J.; Montouillout, V.; Grenèche, J.-M.; Vieillard, P.; Gaucher, E.C.; Fialips, C.I.; Madé, B.
Highlights: A consistent thermodynamic dataset for an illite-smectite (I/S) is acquired by calorimetry. The enthalpies of mixing for a series of I/S minerals are also acquired and results slightly negative. Although small, mixing energies are necessary for the stability of I/S. Abstract: The stability of illite-smectite interstratified with respect to discrete illite and smectite minerals was investigated by measuring their thermodynamic properties. The standard thermodynamic properties of the illite-smectite ISCz-1 mineral ( G, H, S, Cp, and V ) were determined between 298.15 K and 375 K by using calorimetric methods. Moreover, the enthalpies of mixing between the illite and smectite layers were measured at 298.15 K by acid solution calorimetry from a complete series of illite-smectite interstratified minerals (Shinzan area, Japan). The measured values were slightly negative, with a minimum value of −3.7 kJ.mol −1 . This contributed to the stability of the mixed-layer with respect to a mechanical mixture of illite and smectite. In addition, the model from Blanc et al. (2015) was implemented to estimate the thermodynamic properties of the interstratified illite-smectite ISCz-1 mineral. The predicted values were consistent with the experimental results. However, the estimates were slightly improved by considering the thermodynamic properties of the mixture of the illite and smectite components and then adding the terms of energies of mixing. This could be confirmed by establishing the stability domains of ISCz-1 and those of the corresponding illite and smectite end-members according to Meunier and Velde's determination of the smectite to illite reaction pathways (Meunier and Velde, 1989).